THE WAYS OF REFRACTION OF REALITY IN S. DOVLATOV’S WORKS: LIE, DEFAULT AND SILENCE - GAZAROVA, DIANA (Bulletin of Yerevan University H: Russian Philology, 2019)
The article is devoted to the three types of refracted reality: 1) hidden reality (the category of default), 2) changed reality (concept “deception”), 3) unsaid and – as a result – unchanged reality (silence). We suppose that Dovlatov’s heroes prefer the passive type of lie – silence.
Keywords: category of default, category of definiteness-indefiniteness, relative indefiniteness, active and passive lie, concept “deception”, silence